2015
DOI: 10.1016/j.polymdegradstab.2015.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phosphorous-modified silica on the flame retardancy of polypropylene based nanocomposites

Abstract: International audienceSurface modification of various silicas by phosphorous agents was carried out with the aim to use these particles as flame retardant additive in a polypropylene matrice (PP) at low content (10 wt%). Thermal and flammability properties of PP/modified silica (PP-Tm-10%, PP-Zm-10%) were studied using TGA, PCFC and cone calorimeter and compared to those conferred by pure silica (PP-T-10%, PP-Z-10%). Quite surprisingly the untreated fillers induce the most significant reduction of peak of Heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 58 publications
4
23
0
Order By: Relevance
“…This is related to the dispersity of ATH in EVA matrix and has been limitedly improved by adding DOSA directly. Moreover, the synergistic flame‐retardant mechanism of ATH and DOSA which contain phosphor and silicon element plays an important role in the improvement of LOI value . The LOI value of EVA/DIATH composites with 50% DOSA‐immobilized ATH is 31.4 which will meet the requirement of flame retardancy in the electronic appliance.…”
Section: Resultsmentioning
confidence: 99%
“…This is related to the dispersity of ATH in EVA matrix and has been limitedly improved by adding DOSA directly. Moreover, the synergistic flame‐retardant mechanism of ATH and DOSA which contain phosphor and silicon element plays an important role in the improvement of LOI value . The LOI value of EVA/DIATH composites with 50% DOSA‐immobilized ATH is 31.4 which will meet the requirement of flame retardancy in the electronic appliance.…”
Section: Resultsmentioning
confidence: 99%
“…The 13 C NMR spectrum of SiO 2 -NH 2 is showed in Figure 3. During the process of cocondensation, TEOS and APTES are both involved in the buildup of the gel network.…”
Section: Characterizationmentioning
confidence: 99%
“…The most widely used strategy is to introduce organic functional groups. Studies have shown that surface organic modification of the nanoparticles can effectively improve the flame‐retardant efficiency, but the processes of modification are usually solvent‐wasted, and the amount of introduced organic groups is limited. Cocondensation method is a kind of sol‐gel process utilizing organosiloxanes as a comonomer to hydrolyze and cocondense with tetraethylorthosilicate (TEOS) .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, nitrogen‐containing flame retardants can produce non‐flammable non‐toxic gases, thus diluting the oxygen near the flame and inhibiting combustion . Previous researches have demonstrated that flame retardants containing Si, P, and N co‐elements can exhibit the better flame‐retardant efficiency than flame retardants containing P, N, or Si alone . Thus, it is anticipated that mesoporous silica modificated with organic flame retardants consisting of P, N elements could offer better flame retardant properties to inflammable EP.…”
Section: Introductionmentioning
confidence: 99%
“…than flame retardants containing P, N, or Si alone. [22][23][24][25][26] Thus, it is anticipated that mesoporous silica modificated with organic flame retardants consisting of P, N elements could offer better flame retardant properties to inflammable EP.…”
mentioning
confidence: 99%